Ethical Considerations for Gene Drive: Challenges of Balancing Inclusion, Power and Perspectives - Kormos, Ana; Lanzaro, Gregory C.; Bier, Ethan; Santos, Vanilson; Nazaré, Lodney; Pinto, João; Aguiar dos Santos, Adionilde; James, Anthony A. (Frontiers in Bioengineering and Biotechnology, 2022)
Progress in gene-drive research has stimulated discussion and debate on ethical issues including community engagement and consent, policy and governance, and decision-making involved in development and deployment. Many organizations, academic institutions, foundations, and individual professionals have turned their attention to ensuring that these issues are considered prior to the application of gene drive technology. Central topics include co-development of the technology with local stakeholders and communities, and that asymmetry between developers and end-users should be reduced. Important questions include with whom to conduct engagement and how to define community acceptance, develop capacity-building activities, and regulate this technology. Experts, academics, and funders have suggested that global frameworks, standards, and guidelines be developed to direct research in answering these important questions. Additionally, it has been suggested that ethical principles or commitments be established to further guide research practices. The challenging and interesting contradiction that we explore here is that the vast majority of these conversations transpire with little or no input from potential end-users or stakeholders who, we contend, should ultimately determine the fate of the technology in their communities. The question arises, whose concerns regarding marginalization, disempowerment, and inequity should be included in discussions and decisions concerning how inequities are perceived and how they may be addressed? At what stage will true co-development occur and how will opinions, perspectives and knowledge held by low-income country stakeholders be applied in determining answers to the questions regarding the ethics being debated on the academic stage? Our opinion is that the time is now.